1996
DOI: 10.1016/0029-7844(95)00408-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Recurrences of Cervical Intraepithelial Neoplasia in Women With the Human Immunodeficiency Virus

Abstract: In HIV-infected women, CIN may recur despite multiple treatments, and chronic condylomatous changes are common. Innovative therapies for controlling CIN in HIV-infected women are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
3
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(101 citation statements)
references
References 16 publications
4
88
3
6
Order By: Relevance
“…2,8 -11 It has also been observed that women with low CD4 ϩ counts experience greater rates of cervical lesion recurrence and progression when treated by the traditional ablative methods of loop electrosurgical excision procedure or cone biopsy. 9,12,13 With the advent of newer antiretroviral medications and HAART therapy, it became possible to reverse the depletion of CD4 cells in a person infected with HIV. Opposing studies with small numbers of HIV-positive patients have revealed minimal to no effect of antiretroviral agents on the incidence of cervical dysplasia 14 -17 Two of the studies that failed to reveal a positive effect were performed before HAART became the standard of care.…”
mentioning
confidence: 99%
“…2,8 -11 It has also been observed that women with low CD4 ϩ counts experience greater rates of cervical lesion recurrence and progression when treated by the traditional ablative methods of loop electrosurgical excision procedure or cone biopsy. 9,12,13 With the advent of newer antiretroviral medications and HAART therapy, it became possible to reverse the depletion of CD4 cells in a person infected with HIV. Opposing studies with small numbers of HIV-positive patients have revealed minimal to no effect of antiretroviral agents on the incidence of cervical dysplasia 14 -17 Two of the studies that failed to reveal a positive effect were performed before HAART became the standard of care.…”
mentioning
confidence: 99%
“…In planning treatment, it is important to keep in mind the low rate of adherence with follow-up, reported as high as 35-63% in this population (106,109). Although recurrence rates are higher for seropositive women (107,110,111,112), treatment of high grade lesions is similar to that in the general population. A study of 45 HIV-positive women with cervical carcinoma in situ demonstrated a high rate of recurrence, 65% by cytology alone, after either cone biopsy or hysterectomy for treatment (106).…”
Section: Lower Genital Tract Neoplasiasmentioning
confidence: 94%
“…La inmunosupresión, en particular, la depleción de las células TH pueden interactuar con la infección del VPH, incrementando el riesgo del CaCU. Se ha demostrado que las mujeres HIV positivas y fumadoras, y en especial aquellas que tiene niveles bajos de las células TH bajos, tienen un riesgo significativamente elevado de desarrollar o presentar recurrencia de lesiones precancerosas o cancerosa del CU (62).…”
Section: In 2004unclassified